2020
DOI: 10.5114/aoms.2020.94970
|View full text |Cite
|
Sign up to set email alerts
|

Gait disturbances in patients with rheumatoid arthritis

Abstract: IntroductionRheumatoid arthritis (RA) is a chronic inflammation resulting in the involvement of all the structures constituting a joint. We determined the type and severity of foot deformities, determined the impact of the degree of disturbances of foot statics and the disease activity on the duration of the particular phases of gait, determined the impact of the maximum foot load and the percentage distribution of loads between the forefoot and hindfoot on the duration of the particular phases of gait, and es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The increased risk of falls in patients with RA and OA is associated with the presence of pain, joint deformities, limited physical activity and muscle strength, and disturbances in gait and postural control. Proprioception disorders as a component of the postural control system lead to an increased risk of falls [ 41 , 42 , 43 , 44 , 45 ]. In our study, 42.0% of patients with RA and 41.4% of patients with OA had a fall history within the last year, and this rate is in agreement with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of falls in patients with RA and OA is associated with the presence of pain, joint deformities, limited physical activity and muscle strength, and disturbances in gait and postural control. Proprioception disorders as a component of the postural control system lead to an increased risk of falls [ 41 , 42 , 43 , 44 , 45 ]. In our study, 42.0% of patients with RA and 41.4% of patients with OA had a fall history within the last year, and this rate is in agreement with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Foot deformity leads to a partial or, sometimes, total loss of mobility in foot joints and pain, commonly located in the forefoot. Unfortunately, studies have revealed that in many cases this problem is underestimated by family doctors [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing physical activity in RA patients may also be beneficial in fall risk, given that RA gait disturbances may occur [40]. Indeed, balance disturbances in RA patients are positively associated with a risk of falls of 33% [41,42].…”
Section: Completeness and Applicability Of Evidencementioning
confidence: 99%
“…Indeed, balance disturbances in RA patients are positively associated with a risk of falls of 33% [41,42]. Furthermore, lack of physical activity in RA patients lowers their functional ability by approximately 60% in females and 40% in males [40]. Similarly, RA patients may experience sarcopenia (approximately 3-24%), which is associated with falls and poor functional ability [43].…”
Section: Completeness and Applicability Of Evidencementioning
confidence: 99%